Asian theater conversation with A. C. Scott - McMuller, Larry; Scott, A.C.; Michigan State University (Michigan : Michigan State University, 1980)
A.C. Scott elaborates on his long years of experience in China and Japan and shows film clips and slides of his classes, rehearsals and workshop productions in which Asian performers have assisted him in training of American student actors
Title from container
Project director, Farely Richmond ; camera, Jackie Denn, Jim Hamilton
Guest professor: A. C. Scott
DVD format
Keywords: Theater -- Asia; Performing arts -- Asia